2015
DOI: 10.1016/j.bandl.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

EEG potentials associated with artificial grammar learning in the primate brain

Abstract: HighlightsFirst combined EEG and Artificial Grammar (AG) learning study in nonhuman animals.Early and late frontal potentials modulated in response to violations of the AG sequencing relationships in the primate brain.Informative similarities and differences are noted in relation to reported human EEG potentials associated with AG learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…EEG recordings can be obtained from scalp electrodes but the procedure requires daily placement of electrodes on to the scalp along with restraint in primate chairs during the period of recording (Attaheri et al, 2015). An alternative method requires surgical implantation of electrodes into the skull with an acrylic head cap (Woodman et al, 2007) or additionally implanted telemetry devices (Ishikawa et al, 2017; Rachalski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…EEG recordings can be obtained from scalp electrodes but the procedure requires daily placement of electrodes on to the scalp along with restraint in primate chairs during the period of recording (Attaheri et al, 2015). An alternative method requires surgical implantation of electrodes into the skull with an acrylic head cap (Woodman et al, 2007) or additionally implanted telemetry devices (Ishikawa et al, 2017; Rachalski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This title has been chosen to emphasise the re-fuelled interest in the neural dynamics that we measure as fluctuations of electrical neural signalsnon-invasively from the scalp, or invasively directly from neural tissue. It is maybe noteworthy that this issue conjoins both approaches, yet reverses the usual method-to-species assignment: We here present scalp electroencephalography (EEG) data from behaving macaques (Attaheri et al, 2014) and invasive electrocorticography (ECoG) data from human patients undergoing epilepsy treatment (Nourski et al, 2015).…”
mentioning
confidence: 96%
“…Using a very comparable design that also tests contingency extraction, Attaheri et al (2014) provide us with a non-invasive, nonhuman primate model of (artificial) grammar acquisition. They report a frontally-distributed deflection in the ERP around 200 ms, which is potentially homologous to the human violation-indicating MMN response.…”
mentioning
confidence: 99%
“…1, 2 and 4, we can see that for participant P2, during an observation interval between (4-6) min the amplitude of P200 is high (12.67 µV) while the amplitude of N200 is low (−3.04 µV), thereby resulting in 93.48% accuracy. In case of participant P6, during an observation interval between (16)(17)(18) min the amplitude of both P200 and N200 is low and is 2.31 µV and −1.25 µV, respectively, thereby resulting in 71.41% accuracy. In case of participant P1, during an observation interval between (6-8) min the amplitude of P200 is low (1.71 µV) while the amplitude of N200 is high (−7.19 µV), thereby resulting in 81.48% accuracy.…”
Section: Accuracy = T a + T S T A + T S + F A + F Smentioning
confidence: 99%
“…For instance, ERP features namely P100-N200 have been utilized for studying emotional information processing in [11]; frontal midline theta and N200 ERP have been shown to reflect complementary information about expectancy and outcome evaluation in [12]; in [13] authors utilized N200 ERP for word recognition; in [14], N100, P200, N200 and P300 ERP components have been used to study the impact of depression on attention. Further, ERPs have also been used for understanding reaction times in response to pictures of people depicting pain [15]; in [16] ERPs have been utilized to understand the state of brain in schizophrenia patients; in [17] authors demonstrated the association of mMMN, P200 and P500 ERP components with artificial grammar learning in the primate brain; in [18], N400 and the P200 components have been utilized in the investigation of semantic and phonological processing in skilled and less-skilled comprehenders; besides, ERPs have also found utility in studying multisensory integration (MSI) ability of the brain in school-aged children [19].…”
Section: Introductionmentioning
confidence: 99%